2010
DOI: 10.1101/gad.550010
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional factor ENY2 is associated with the THO complex and promotes its recruitment onto nascent mRNA

Abstract: Metazoan E(y)2/ENY2 is a multifunctional protein important for transcription activation and mRNA export, being a component of SAGA/TFTC and the mRNA export complex AMEX. Here, we show that ENY2 in Drosophila is also stably associated with THO, the complex involved in mRNP biogenesis. The ENY2-THO complex is required for normal Drosophila development, functioning independently on SAGA and AMEX. ENY2 and THO arrive on the transcribed region of the hsp70 gene after its activation, and ENY2 plays an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 44 publications
6
70
0
3
Order By: Relevance
“…Recent studies using conditional knockout or a hypomorphic mutant mouse model have provided evidence that the THO complex has specific roles in cell differentiation during development (Mancini et al, 2010;Wang et al, 2009;Wang et al, 2007). It has also recently been reported that the Drosophila THO complex is required for normal development through collaboration with E(Y)2 (or ENY2), a multifunctional protein important for transcription activation and mRNA export (Kopytova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies using conditional knockout or a hypomorphic mutant mouse model have provided evidence that the THO complex has specific roles in cell differentiation during development (Mancini et al, 2010;Wang et al, 2009;Wang et al, 2007). It has also recently been reported that the Drosophila THO complex is required for normal development through collaboration with E(Y)2 (or ENY2), a multifunctional protein important for transcription activation and mRNA export (Kopytova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Primary antibodies used in this study were: anti-THOC7 (Kim et al, 2011) at 1:1000, anti-HPR1 (Rehwinkel et al, 2004) at 1:100, anti-THO2 (Rehwinkel et al, 2004) at 1:100, anti-THOC5 (Kopytova et al, 2010) at 1:100 and anti-Fibrillarin (38F3; Santa Cruz, sc-56676) at 1:50. The secondary antibodies Alexa 546-conjugated goat anti-rabbit (1:500) and Alexa 488-conjugated goat anti-mouse (1:500) were purchased from Molecular Probes.…”
Section: Antibody Staining and Microscopymentioning
confidence: 99%
“…It is tethered to the inner side of the nuclear pore complex (NPC) via AtNUP1 (also named NUP136) which is a plant-specific nucleoporin. 14,17 Similar TREX-2 homologs have also been identified in fruit flies 18 and humans. 19 Here, we present evidence demonstrating a physical link between Arabidopsis UCH1/UCH2 and the 26S proteasome lid complex, as well as to the TREX-2 complex.…”
mentioning
confidence: 96%
“…95 However, the association of ENY2 with components of THO instead of TREX-2 suggests that Sus1/ENY2 may participate in mRNA export, in conjunction with similar but somewhat different complexes, in higher eukaryotic cells. 96 Nevertheless, as compared with yeast, the detailed function of TREX and related complexes in higher eukaryotes is less clear and requires much more investigation.…”
Section: Introductionmentioning
confidence: 99%